12 modern philosophers - Belshaw, Christopher; Kemp, Gary (Wiley-Blackwell, 2009)
Featuring essays from leading philosophical scholars, 12 Modern Philosophers explores the works, origins, and influences of twelve of the most important late 20th Century philosophers working in the analytic tradition. Draws on essays from well-known scholars, including Thomas Baldwin, Catherine Wilson, Adrian Moore and Lori Gruen Locates the authors and their oeuvre within the context of the discipline as a whole Considers how contemporary philosophy both draws from, and contributes to, the broader intellectual and cultural milieu